Accelerating the reaction kinetics of lithium–oxygen chemistry by modulating electron acceptance–donation interaction in electrocatalysts. Issue 33 (12th August 2022) - Zhao, Chuan; Long, Jianping; Zhou, Bo; Zheng, Ruixin; He, Miao; Li, Runjing; Pan, Yu; Hu, Anjun; Shu, Chaozhu
Abstract : The 3d-orbital electron occupancy degree of Zn sites can be reduced by Co doping, which optimizes the electron acceptance-donation interaction between Zn sites and reactants, and thus weakens the energy barrier of Li2 O2 deposition and decomposition. Abstract : Lithium–oxygen batteries (LOBs) have presented great promise in next-generation energy storage systems due to their high theoretical energy density. However, the sluggish deposition and decomposition kinetics of lithium peroxide (Li2 O2 ) on the oxygen electrode inhibits the practical application of this type of novel power source. Herein, Co-doped Zn based zeolite imidazole framework (ZIF) nanosheets are elaborately designed and used as oxygen electrode catalysts to boost the performance of LOBs. The incorporation of Co rationally regulates the 3d-orbital electron occupation of Zn sites, which results in an appropriate electron acceptance–donation interaction between Zn sites and reactants, thus achieving the efficient activation of reactants. The optimized electronic structure of Zn sites is also capable of modulating the product morphology, resulting in the formation of unique rose-like Li2 O2, which guarantees efficient mass and charge transfer and establishes a superior reaction interface between discharge products and electrodes. By virtue of these merits, the LOBs with the Zn0.8 Co0.2 ZIF electrode deliver a high discharge/charge capacity (12 950.7/12 916.8 mA h g −1 ), low overpotential (0.92 V) and outstanding cycling stability (over 500 cycles). This work provides unique insights into the design of advanced catalysts to accelerate oxygen electrode reactions at the orbital level.